MUSIK GAMBANG KROMONG SEBAGAI IRINGAN LENONG BETAWI - Sukotjo . (SELONDING, 2012)
Gambang Kromong music of Batavian in Jakarta plays a vital role in directing the mood of a Lenong play scene. Each scene staged in Lenong is accompanied by Gambang Kromong music to illustrate the sad, happy, and other moods in the performance. The interactive process between Gambang Kromong players and the Lenong characters is manifested in a mutual understanding of each scene. The performance of Lenong Betawi needs the support the accompanying Gambang Kromong ensemble.   Keywords: Gambang Kromong Music, Scene, Lenong